Roland Barthes, 1947-1960: journalism, sociology and the popular theatre - Stafford, Andy (1995)
This thesis situates the writings of Roland Barthes in the immediate postwar period. Whilst Barthes's thought has generally been appreciated for its theoretical innovations, this study identifies the historical and cultural influences behind his theories. His first permanent job in 1960, at the age of forty-five, ended a decade of career and financial uncertainties, during which he had been, above all, a journalist. His most famous book, Mythologies, consists of articles which were originally part of a monthly column appearing in the left-wing journal Les Lettres nouvelles between 1954 and 1956; this column helped to inflect the journal's attitude towards events such as decolonization. At the same time, he was active in the popular theatre movement, writing for Theatre populaire and defending Brechtian theatre. Barthes was also a pioneer of analytical tools in the social sciences. An avid reader of Michelet's attempts to 'resurrect' those who had been excluded by traditional historical narratives, Barthes valued the new history-writing of the Annales. He suggested a historical materialist analysis which, underlining the voluntarist nature of history, tried to resolve two historiographical dilemmas. Firstly, how could historical representation incorporate both continuity and change? Secondly, could a scientific, objective description of reality be reconciled with its partisan, subjective explanation? Undermining his earlier voluntarist view of history, the first dilemma was resolved by semiology: change and continuity were reconciled by showing forms functioning in a system. In the second the committed sociologist and critic could use the 'dialectique d'amour' to denounce and explain the alienation caused by bourgeois myths. However, whilst developing his semiological analysis, Barthes also concluded that a representation of both subjective and objective reality led to the exclusion of the committed critic. Finally, this thesis will suggest how Barthes's experiences and theoretical developments can be linked to his political views in this immediate postwar period.